Peningkatan Kadar Kolesterol dan Usia Pada Ibu Rumah Tangga - Fajar Husen; Nuniek Ina Ratnaningtyas; Nur Aini Hidayah Khasanah; Nilasari Indah Yuniati (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction; Cholesterol is a metabolite of fat that contains sterol compounds and is primarily concentrated in cell membranes in the body and the circulatory system. Purpose; To determine the total cholesterol level in homemakers (IRT) based on the age range category of 25-80 years and the relationship between increasing total cholesterol levels with the age of IRT. Method; The research method is descriptive-analytical with a cross-sectional approach, with a total sample of 30 and the sampling technique is purposive sampling. Data on the relationship between total cholesterol levels and age were statistically analyzed by bivariate analysis with the Pearson correlation index on SPSS software. Results; Total of 30 IR respondents, the average cholesterol level was 198.07 mg/dL, and the average age was 47.87 years. 50% of respondents have good cholesterol levels, 26.67% in the border category, and 23.33% in the danger category, with the highest cholesterol levels being 297 mg/dL and the lowest being 130 mg/dL. Conclusion; Total cholesterol levels in IRT in Tanjung are dominated by women over 45 years, with cholesterol levels ranging from 130 to 300 mg/dL, and there is a strong relationship between increased cholesterol levels in the body and rising age